2016
DOI: 10.1007/s00253-016-7984-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals on aerobic denitrification by strain Pseudomonas stutzeri PCN-1

Abstract: Effects of heavy metals on aerobic denitrification have been poorly understood compared with their impacts on anaerobic denitrification. This paper presented effects of four heavy metals (Cd(II), Cu(II), Ni(II), and Zn(II)) on aerobic denitrification by a novel aerobic denitrifying strain Pseudomonas stutzeri PCN-1. Results indicated that aerobic denitrifying activity decreased with increasing heavy metal concentrations due to their corresponding inhibition on the denitrifying gene expression characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…Proteins of denitrication cascade which is not active, obviously, can protect microbial cells against heavy metals. In accordance with our observation Gui et al 45 found that aerobic denitrication was inhibited with heavy metals, including cadmium. Based on the similarity of ionic radii, Cd 2+ probably replaced mercury in mercuric transport protein (MERP).…”
Section: Metalloproteinssupporting
confidence: 93%
“…Proteins of denitrication cascade which is not active, obviously, can protect microbial cells against heavy metals. In accordance with our observation Gui et al 45 found that aerobic denitrication was inhibited with heavy metals, including cadmium. Based on the similarity of ionic radii, Cd 2+ probably replaced mercury in mercuric transport protein (MERP).…”
Section: Metalloproteinssupporting
confidence: 93%
“…2b). This experiment phenomenon, which was similar to that of nitrate aerobic denitrification by Pseudomonas stutzeri PCN-1 under 2.5 mg L −1 Cd(II), 5 mg L −1 Cu(II) or 10 mg L −1 Ni(II) (Gui et al 2017), implied that the CoHis absorbent with a His/Co 2+ of 2 had stronger inhibition effect on the activity of nitrite reductase than of nitrate reductase. In the EG-nitrite, the reduction of nitrite was very slow over the entire experiment, with a final removal efficiency of 13% (Fig.…”
Section: Resultssupporting
confidence: 66%
“…When the His/Co 2+ rose to 3, LYM could transfer 96% initial nitrate (150 mg L −1 , 10.7 mM) to nitrite within 6.3 h. As an intermediate of denitrification, nitrite accumulated to as much as 141 mg L −1 in 6.3 h, which was probably caused by the time lag between the highest activity level of nitrate reductase and nitrite reductase (Gui et al 2017). The accumulated nitrite was reduced with a distinctly slower rate than in the CG, and the decrease of accumulated nitrite stopped at 20 mg L −1 after 48 h. The reduction of added nitrite was fast in 0–24 h with a rate slower than in the CG, then slowed down, and finally stopped at 6 mg L −1 after 48 h. The descent of cobalt(II) was fast in 0–6 h and slowed down in the following time, manifesting a plateau in the middle period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in literature show the presence of heavy metals such as zinc (Zn +2 ), nickel (Ni +2 ) and cadmium (Cd +2 ) inhibit the expression of nosZ, especially copper (Cu +2 ) (at concentrations ≥ 0.5 mg L -1 ) (Gui et al, 2017). This gene is responsible for the activation of N2O reductase, an enzyme that catalyzes the reduction of N2O to N2 and is activated by nosZ (Figure 3).…”
Section: Heavy Metal Presencementioning
confidence: 99%